Optimizing curing parameters to enhanced the compressive strength and toughness properties of Resin-Coated Sand (RCS) in foundry applications - Ampala Khoryanton; Sri Harmanto; Ahmad Mamba’udin; Abdul Syukur Alfauzi; Hery Tristijanto; Zaenal Abidin; Padang Yanuar; Farika Tono Putri; Wahyu Isti Nugroho; Timotius Anggit Kristiawan; Friska Ayu Fitriani Sugiono; Iman Mujiarto; Elfrida Rizky Riadini; Yuris Bahadur Wirawan (Jurnal Polimesin, 2025)
Conventional heating methods remain prevalent among small and medium-sized enterprises (SMEs) for aluminum mold thermal regulation during resin-coated sand (RCS) core production. Inconsistent thermal regulation significantly alters the characteristics of resin-coated sand cores. This study aims to investigate the effect of curing parameters on the compressive strength and toughness of the resin-coated sand. The RCS specimens were prepared using an aluminum mold that underwent controlled thermal treatment in an electrical furnace. The thermal treatment is performed by processing specimens across a curing temperature range of 200-300Â°C and varying curing time from 3 to 15 minutes. HDPE polymer was proposed as the RCS binder. Compressive and impact tests were carried out to determine the characteristics of resin-coated sand. The results showed a non-linear relationship between curing parameters and mechanical properties. Although moderate curing time and higher temperatures initially improve compressive strength and toughness, exceeding optimal thresholds leads to the degradation of these mechanical characteristics. The highest mechanical properties (compressive strength = 38.4 MPa, toughness = 0.43 MPa) are achieved through a curing temperature of 250Â°C and a curing time of 9 minutes. This study provides valuable insights into determining the optimal parameters for processing resin-coated sand cores or molds with superior compressive and toughness properties.